How Should We Balance Domestic and Foreign Debts in Order to Avoid Debt Trap? - Fujita, Yasunori (Archives of Business Research, 2023)
Many attempts have been made to examine the effect of debts on economic growth, in order to find out the ways to avoid debt trap, where national revenue is obliged to be spent mainly for repaying debts rather than constructing infrastructures for long-term economic development, making it even more difficult to repay the debts, like Sri Lanka that fell into its worst financial crisis in 2022. In the present paper, we explore the proper debt management to avoid the debt trap, by laying out a theoretical model that incorporates both domestic and foreign debts based on Fujita (2022) and Padoan et al (2012). Main results we obtain are summarized as follows. (1) In order to avoid the debt trap, in accordance with increase in ratio of domestic debt to GDP, , government should increase ratio of foreign debt to GDP, up to certain level of , , and reduce after that. (2) if domestic interest rate does not increase so much in accordance with increase in difference of growth rates of domestic debt and GDP, government should reduce if foreign interest rate increases; if domestic interest rate increases sharply in accordance with increase in difference of growth rates of domestic debt and GDP, government should increase if foreign interest rate increases.